Effectiveness of use of Nanostructure Minerals – Bentonite of Taganskiy Deposit for Waste Water Clearing in Metallurgy Industry - Muzdybayeva, Sharbanu; Musabekov, K.; Muzdybayev, N.; Askarova, Gaukhar; Nurbaeva, N.; Taybaeva, P. (European Journal of Sustainable Development, 2014)
The currently used traditional method of waste water treatment based on the precipitation of heavy metals by iron hydroxide formed at the time of neutralization (liming) / bleach (active chlorine) doesn’t correspondent to the standards of maximum permissible concentration (MPC) in practical meaning. In this regard, the urgent task is the use of natural materials as sorbents due to the relatively high sorption capacity, selectivity, having cation-exchange properties and the possibility of almost complete removal of heavy metal ions. Another important factor is their relatively low cost and availability (sometimes as a local material). We believe that the use of scientific-based combinations of different ways in waste water treatment based on the success of modern chemistry allows opening new and perspective opportunities in this area. Key Words: Waste Water, Metallurgy, Bentonite, Zeolites, Groundwater